THE INFLUENCE OF EDUCATORS’ COMMUNICATION SKILLS, EMOTIONAL MATURITY, AND NON-DISCRIMINATION ATTITUDES ON LEARNERS’ MOTIVATION IN NON-FORMAL EQUIVALENCY EDUCATION IN INDONESIA - Rudi Amir; Kartini Marzuki; Nasrah Natsir; Nirwana Nirwana; Sri Nurhayati; Gumpanat Boriboon; Damola Olugbade; Khalid Ilias Basheer Qolamani (Program Studi PGSD Universitas Flores, 2026)
This study investigated the relationship between educators’ communication skills, emotional maturity, and non-discrimination attitudes and their influence on learner motivation in equivalency education programs at SPNF SKB Takalar, Indonesia. Equivalency education, designed to provide alternative pathways for individuals who did not complete formal schooling, requires sustained learner motivation to achieve its social and educational goals. The study aimed to identify the extent to which these three educator attributes contribute to learner engagement and persistence. A quantitative descriptive-correlational design was employed. The population included 115 learners enrolled in equivalency programs, with a random sample of 40 participants. Data were collected using structured questionnaires assessing communication skills, emotional maturity, non-discrimination attitudes, and learner motivation. Statistical analysis involved descriptive measures and Pearson product-moment correlations to examine associations among the variables. Findings revealed that all three attributes were rated as “fairly good” by learners and significantly correlated with learner motivation. Communication skills emerged as the strongest predictor, highlighting the importance of clarity, immediacy, and relational engagement. Emotional maturity demonstrated a strong link with motivation, emphasizing empathy, resilience, and regulation in shaping supportive classroom climates. Non-discrimination attitudes were also significant, underscoring the role of fairness and inclusivity in fostering learners’ confidence and persistence.